2021
DOI: 10.7759/cureus.14884
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatocellular Carcinoma in Hispanics and Non-Hispanics Patients

Abstract: Background: Hepatocellular carcinoma (HCC) is the fastest growing cancer in the United States. Studies have shown that compared to Blacks and non-Hispanic Whites, Hispanics have a higher HCC incidence and mortality rate. Most studies investigating HCC in Hispanics have been conducted utilizing data largely from the Western and Southern United States. These findings may, however, not be highly representative of Hispanics in the Northeast, given the nonhomogenous distribution and diversity of Hispanics across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Mexican American probands with HCC in our cohort had a high prevalence of obesity, diabetes, hypertension and hypercholesterolemia, which corroborates previous studies characterising Hispanic Americans with HCC 2,4,26–28 . Several population‐based studies have indicated that there may a hereditary component of hepatic steatosis and fibrosis 29–32 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Mexican American probands with HCC in our cohort had a high prevalence of obesity, diabetes, hypertension and hypercholesterolemia, which corroborates previous studies characterising Hispanic Americans with HCC 2,4,26–28 . Several population‐based studies have indicated that there may a hereditary component of hepatic steatosis and fibrosis 29–32 .…”
Section: Discussionsupporting
confidence: 90%
“…Mexican American probands with HCC in our cohort had a high prevalence of obesity, diabetes, hypertension and hypercholesterolemia, which corroborates previous studies characterising Hispanic Americans with HCC. 2,4,[26][27][28] Several population-based studies have indicated that there may a hereditary component of hepatic steatosis and fibrosis. [29][30][31][32] Our group has also previously demonstrated an increased incidence of hepatic fibrosis in the first-degree relatives of patients with cirrhosis secondary to nonalcoholic fatty liver disease (NAFLD).…”
Section: Ta B L E 4 Characteristics Of Firstdegree Relatives With Def...mentioning
confidence: 99%
See 2 more Smart Citations